USE OF PEDAGOGICAL TEHNOLOGIES IN PHYSICAL EDUCATION LESSONS (ON THE EXAMPLE OF FOOTBALL LESSONS) (American Journal of Pedagogical and Educational Research, 2023)
The article discusses the use of innovative technologies in physical education and football lessons. Since football is the most popular sport